"ESTUDO SOBRE ÁREAS DE FIGURAS PLANAS, COM EMPREGO DE MÉTODOS E RECURSOS VARIADOS." - Leila da Silva Santos (2023)
Santos, Leila. Study on areas of flat figures, using varied methods and resources. Dissertation (PROFESSIONAL MASTER) – Federal University of Mato Grosso do Sul, Três Lagoas campus, Mato Grosso do Sul, 2023. The main objective of this dissertation is to contribute to a quality and inclusive education. This contribution will be through a study on Areas of Flat Figures, with the use of several resources and methodologies. The concept of area will be addressed in a concrete, contextualized and inclusive way. This work, although it may seem like it, is not about inclusion or how to work on certain content with students with some type of disability. It's about the study of Areas of Plane Figures and how to teach it, in a simple, concrete way, in which everyone learns, whether or not they have a disability. For this, some techniques for area calculation are presented, which can be deepened, according to the progress of each class. Key words: Area. Learning. Flat Figures. Polygons. Resources. Pick's theorem. Excess and Lack Method. Tangram. Polygon Decomposition. Gauss method. Shoelace Rule.